Prioritising community-defined interventions to address the health and well-being impact of the COVID-19 pandemic on racially minoritised communities in East London: results from an adapted James Lind Alliance priority setting partnership - Isabelle Whelan; Chloe Orkin; Vanessa Apea; Suzannah Kinsella (BMJ Open)
Objectives Racially minoritised communities (RMCs) were disproportionately affected by COVID-19, experiencing among the highest mortality rates of the UK’s pandemic. We sought to understand the priorities for action to address the impact of the COVID-19 pandemic on the health and well-being of RMCs in the ethnically diverse and socioeconomically unequal area of East London, located in the northeastern part of London, England.Design Prospective surveys and a consensus meeting following the established James Lind Alliance priority setting partnership (PSP) methodology, adapted for a specific geographic location and ethnic groups.Setting Conducted in East London between 2021 and 2023.Participants Participants were individuals aged ≥18 years living and/or working in East London. Communities represented included Black African, Black Caribbean, Somali, South Asian and Bangladeshi.Outcome measure People were asked to submit suggestions for the priorities for action to address the impact of the COVID-19 pandemic. Return responses were reviewed and prioritised in a final workshop.Results 816 suggestions were gathered from 187 responses to the initial survey. These were summarised into a longlist of 40 for the second survey, from which 243 respondents identified a shortlist of 26 priorities for discussion in a consensus meeting. The final top 10 priorities cover community-based support and spaces spanning education, social support, mental health and housing.Conclusion A systematic methodology was used to identify the priorities of RMCs in East London in the context of recovery from the COVID-19 pandemic. The breadth of the top 10 reflects how profound the effects of the pandemic have been among these communities. It also demonstrates the capacity of a PSP to articulate diverse community-driven priorities for a topic that was wider than healthcare. The findings could have applications in other disease areas that disproportionately affect RMCs.